2021
DOI: 10.1063/5.0038749
|View full text |Cite
|
Sign up to set email alerts
|

Connecting real glasses to mean-field models

Abstract: We propose a novel model for a glass-forming liquid, which allows us to switch in a continuous manner from a standard three-dimensional liquid to a fully connected mean-field model. This is achieved by introducing k additional particle–particle interactions, which thus augments the effective number of neighbors of each particle. Our computer simulations of this system show that the structure of the liquid does not change with the introduction of these pseudo-neighbors and by means of analytical calculations, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…For all the systems, the data are plotted below their respective onset temperatures (see Table I). 27 The systems follow the expected linear relationship between TSc and T (Fig. 4).…”
Section: Configurational Entropymentioning
confidence: 71%
See 4 more Smart Citations
“…For all the systems, the data are plotted below their respective onset temperatures (see Table I). 27 The systems follow the expected linear relationship between TSc and T (Fig. 4).…”
Section: Configurational Entropymentioning
confidence: 71%
“…We find that the excess entropy decreases with increasing k. Our earlier study showed that with increasing k, the structure of the system remains unchanged. 27 Thus, the contribution of the regular neighbors to the entropy does not change with k. However, with an increase in the number of pseudoneighbors and thus U pseudo k , the total excess entropy decreases. Thus, the decrease in excess entropy obtained via the TI method can be attributed to the increase in the pseudoneighbor interactions.…”
Section: Excess Entropymentioning
confidence: 93%
See 3 more Smart Citations